Projected art history : biopics, celebrity culture, and the popularizing of American art - Berger, Doris (International Texts in Critical Media Aesthetics ;, 2014)
"Biopics on artists have an enormous effect on the popular understanding of what it means to be an artist. Projected Art History highlights the narrative structure and images created in the film genre of biopics, in which the artist's life is being dramatized and embodied by an actor. Doris Berger bridges a gap between art history, film studies and popular culture by investigating how the film genre of biopics adapts written biographies and projects art history for a mass audience. Berger offers an analytical approach by concentrating on the two case studies Basquiat (1996) and Pollock (2000), but also looks at larger issues at play, such as how postwar American art history is being mediated in a popular format such as the biopic. This is the first book to identify the functionality of the biopic film genre and showcase its implication for a popular art history that is projected on the big screen"--